Psychological Resilience and Career Success of Female Nurses in Central China: The Mediating Role of Craftsmanship - Xue, Huiyuan; Si, Xiaona; Wang, He; Song, Xiaoren; Zhu, Keke; Liu, Xiaoli; Zhang, Fen (Frontiers in Psychology, 2022)
Background Nurses’ career success is an important factor affecting the quality of nursing services and the stability of the nursing workforce, and enhancing nurses’ career success level is of key significance to the development of the nursing discipline. As psychological resilience and craftsmanship are important spiritual traits in the process of nurses’ career development, it is important to understand the mechanism of their effects on nurses’ career success level. Objective To explore the current situation of craftsmanship, psychological resilience and career success levels of female nurses in central China, and to verify the mediating role of craftsmanship between psychological resilience and female career success using structural equation model. Methods A cross-sectional study was conducted among 2359 female nurses from three hospitals in central China through an online questionnaire, including craftsmanship, psychological resilience and career success scale. The data were analyzed by Z-test and Spearman rank correlation with SPSS 23.0 statistical software, and the mechanism of the effect of craftsmanship and psychological resilience on career success was completed by AMOS 23.0 statistical software. Results The scores of career success, psychological resilience, and craftsmanship of female nurses in central China were 68.00 (61.00, 75.00), 74.00 (64.00, 84.00), and 83.00 (79.00, 95.25). Spearman rank correlation analysis showed that Chinese female nurses’ career success was positively correlated with craftsmanship (r = 0.511, P < 0.01) and psychological resilience (r = 0.595, P < 0.01). Craftsmanship played a mediating role between psychological resilience and career success, accounting for 39.3% of the total effect ratio. Conclusion The scores of career success and psychological resilience of female nurses in central China are at a moderate level, and craftsmanship plays a mediating role between psychological resilience and career success. It is suggested that nursing managers should pay attention to the importance of career success to nurses’ self-development and nursing team stability, and improve their sense of career success by effectively improving nurses’ psychological resilience and craftsmanship.